Knowledge, Attitude, Perception of Biological Science and Healthcare Professional Students to Complementary and Alternative Medicine Health Belief and Practice in Southeastern Region of Bangladesh: A Comparative Study - Reza, ASM Ali; Sikdar, Nahid; Nasrin, Mst Samima; Rahman, Md Atiar; Tareq, Abu Montakim; Alam, AHM Khurshid; Sharmin, Sanjida; Sayeed, Mohammed Abu (Bangladesh Pharmaceutical Journal, 2021)
The health professionals require scientific knowledge to advise their patients on complementary and alternative medicines (CAM). Previously, several studies were conducted regarding the CAM perception, attitude and use on health care professionals only; in contrast, our study encompasses both students of health care professionals and other disciplines. The aim of this study was to compare the attitudes and perception about CAM practices between students of biological sciences (Biochemistry and Molecular Biology, Microbiology and Botany) and health care professionals (Pharmacy and medical students) in public and private universities located in the southeastern region in Bangladesh. The questionnaire-based study conducted on 332 systematically sampled students (four private and one public universities) located in the southeastern region in Bangladesh. The cross-sectional study was conducted from March to July, 2018. All students showed a positive attitude towards CAM use. Herbal medicine, homeopathy, nutritional supplements followed by hypnosis, massage, spiritual healing, and meditation were the most commonly known and used CAM modalities. Most of the students (40.7%) believed that the integration of CAM and conventional medicine should be essential in health care setting. The major obstacles for CAM use are patient interest (48.2%) and lack of physician interest (43.4%). In addition, 36.7% students believed that CAM practices should be included in their school’s curriculum. Moreover, 39.5% students assumed that CAM knowledge is important to their daily life. Biological sciences and healthcare professional students of Bangladesh showed positive perception on CAM uses. Bangladesh Pharmaceutical Journal 24(2): 159-167, 2021